RNA interference technology in crop protection against arthropod pests, pathogens and nematodes - Zotti, Moises; dos Santos, Ericmar Avila; Cagliari, Deise; Christiaens, Olivier; Taning, Clauvis Nji Tizi; Smagghe, Guy (Pest management science, 2018)
Scientists have made significant progress in understanding and unraveling several aspects of double‐stranded RNA (dsRNA)‐mediated gene silencing during the last two decades. Now that the RNA interference (RNAi) mechanism is well understood, it is time to consider how to apply the acquired knowledge to agriculture and crop protection. Some RNAi‐based products are already available for farmers and more are expected to reach the market soon. Tailor‐made dsRNA as an active ingredient for biopesticide formulations is considered a raw material that can be used for diverse purposes, from pest control and bee protection against viruses to pesticide resistance management. The RNAi mechanism works at the messenger RNA (mRNA) level, exploiting a sequence‐dependent mode of action, which makes it unique in potency and selectivity compared with conventional agrochemicals. Furthermore, the use of RNAi in crop protection can be achieved by employing plant‐incorporated protectants through plant transformation, but also by non‐transformative strategies such as the use of formulations of sprayable RNAs as direct control agents, resistance factor repressors or developmental disruptors. In this review, RNAi is presented in an agricultural context (discussing products that have been launched on the market or will soon be available), and we go beyond the classical presentation of successful examples of RNAi in pest‐insect control and comprehensively explore its potential for the control of plant pathogens, nematodes and mites, and to fight against diseases and parasites in beneficial insects. Moreover, we also discuss its use as a repressor for the management of pesticide‐resistant weeds and insects. Finally, this review reports on the advances in non‐transformative dsRNA delivery and the production costs of dsRNA, and discusses environmental considerations. © 2017 Society of Chemical Industry Easy and cheap production, efficient delivery, bioinformatics for biosafety and selectivity in design of dsRNA. Control of pest insects, mites, ticks, plant pathogenic fungi, root‐knot nematodes, weeds and viruses.